2016
DOI: 10.1039/c6ce01712f
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth and physical properties of the organic salt benzimidazolium 3-nitrophthalate

Abstract: From the point of view of crystal growth and design, it is interesting to study the effect of different isomers on the resulting structure. Single crystals of the organic salt benzimidazolium 3-nitrophthalate (BZD + •mNPA − ) have been grown by slow evaporation from methanol solution. Single crystal X-ray diffraction demonstrated that the crystal structure belongs to the monoclinic system with space group P2 1 /c. The properties of the functional groups have been studied by FTIR spectroscopy, FT-Raman spectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 50 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…In AHMP molecule, the d CH3 is identified at 1.99 ppm. In the simulated 1 H NMR spectrum, the signals due to H25 and H22 hydrogens are found at 15.78 ppm and 13.42 ppm which indicate the existence of strong NeH þ /O À and NeH/O hydrogen bonds, respectively in the PDCA À .AHMP þ[67,68]. However these signals were not observed in recorded 1 H NMR spectrum because it was measured in the 0e10 ppm region.…”
mentioning
confidence: 94%
“…In AHMP molecule, the d CH3 is identified at 1.99 ppm. In the simulated 1 H NMR spectrum, the signals due to H25 and H22 hydrogens are found at 15.78 ppm and 13.42 ppm which indicate the existence of strong NeH þ /O À and NeH/O hydrogen bonds, respectively in the PDCA À .AHMP þ[67,68]. However these signals were not observed in recorded 1 H NMR spectrum because it was measured in the 0e10 ppm region.…”
mentioning
confidence: 94%
“…Pogorzelec-Glaser et al 30 studied the formation of benzimidazole salts with dicarboxylic acids (glutaric and pimelic acids), showing that NH⋯O hydrogen bonds link the two different molecules present in the crystal. The benzimidazole salt and 3-nitrophthalic acid were reported and characterized by Mekala et al , 31 who showed that the ions were connected via strong N–H⋯O interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In an approach to develop pharmaceutical compound, improvisation of the physicochemical properties of drugs are needful. Recent research works on cocrystals have drawn much attention toward pharmaceutical applications where properties such as solubility, dissolution rate, bioavailability, hardness (or tableting), and stability of a drug can be improved leaving the chemical properties of pure API unchanged ( Chan et al, 2013 ; Dudenko et al, 2013 ; Pagire et al, 2013 ; Sarma and Saikia, 2014 ; Mekala et al, 2016 ; Saikia et al, 2016 ). Cocrystals are crystalline materials composed of multiple components, one being an API and other being a pharmaceutically acceptable coformer connected via hydrogen bond, halogen bonds, and π−π interactions ( Ali et al, 2012 ; Pandey et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%